Multiple Sclerosis and Seizure Prevalence - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Oslo University Hospital and other centers in Norway studied changes in the prevalence and incidence of multiple sclerosis (MS) in Vestfold County, Norway, in the period 1983-2003.